"Find good managers": EPIC interview: Jimena García‐Romeu, CEO of Alcyon Photonics. Issue 5 (1st October 2021) - Pozo, Jose
Abstract: Jose Pozo, EPIC's CTO, talks to Jimena García‐Romeu, CEO of Alcyon Photonics, a provider of photonic building blocks, PDKs and simulation software to aid PIC design and fabrication.